Temporal changes in a community of dung beetles (Insecta: Coleoptera: Scarabaeinae) resulting from the modification and fragmentation of tropical rain forest - Quintero, Ingrid; Halffter, Gonzalo (Instituto de Ecología, A.C., 2009)
In order to determine the changes in biological diversity over time in different habitats of a fragmented tropical rain forest in Manaus, Brazil, we compared capture data from two windows in time: 1986 and 2000. We used beetles of the subfamily Scarabaeinae as an indicator group. Both sets of samples were collected from the same sites and following the same methodology. The only difference was that in 2000 most of the pastures that had been created as isolation barriers had been replaced by secondary vegetation in different stages of development. Beetles were collected from the following habitats: pasture, secondary vegetation, 1 ha, and 10 ha fragments of forest, and continuous rainforest. The main results follow. 1) After the dramatic decrease in Scarabaeinae species richness that followed the creation of the pastures and the isolation of the fragments there was a notable recovery of biodiversity. We associate this with the enormous tract of continuous rainforest that surrounds the study area since the sites were recolonized by rainforest species. 2) The high number of tourist species recorded for the pastures is evidence of the ease with which Scarabaeinae can overcome the physical barriers imposed by fragmentation. Over time, many of the tourist species coming from the intact forest can become colonizers. 3) Even when there is no human intervention, there is a high degree of heterogeneity in the spatial and temporal distributions of the Scarabaeinae in the rainforest. 4) For coprophagous beetles, the effects of forest fragmentation are a function of both forest fragment size and the nature of the matrix in which the fragments occur. In our study the development of secondary vegetation favored the connection between fragments and the continuous forest.